Characterising skeletopathy in an animal model of type 2 diabetes - Dlamini, Gcwalisile Frances (University of the Witwatersrand, Johannesburg, 2022)
Type two diabetes (T2D) is a chronic, progressive heterogonous syndrome with a genetic and environmental origin. It is now recognized as an epidemic with a high morbidity and mortality rate. The endocrinology of type 2 diabetes (T2D) and its predisposing factors have been studied extensively, while diabetic skeletopathy has received negligible research. Previous studies report that fractures in T2D vary with specific sub regions in bones, therefore prompting our study to focus mainly on the femoral head and neck as well as the humerus head. Femoral neck fractures are the commonest, followed by the proximal femur, distal radius and proximal humerus. Susceptibility to fracture is a sequelae of poor bone remodeling. Poor bone remodeling is established at molecular and cellular levels. It depends on the activity of osteoblasts, osteocytes and osteoclasts, which are under the influence of TGF-β1, a pro-osteogenic cytokine, together with BMP3, an anti-osteogenic cytokine. T2D induced bone marrow adipocity and the accumulation of AGEs in cortical bone have also been implicated in increasing susceptibility to fracture. It is still unclear how T2D affects molecular and cellular elements that culminate in weaker bones observed in diabetic patients. In addition, it is debatable if T2D affects the skeleton at disease onset or later in the disease. Therefore, this study aimed to characterize T2D induced skeletopathy and related it to age, in the Zucker Diabetic Sprague Dawley (ZDSD) rat, using the femur and humerus. This study initially confirmed the diabetic state by monitoring animal weights, fasting blood glucose levels, and fasting oral glucose tolerance tests (OGTTs) every fortnight. Then triglyceride levels and quantified serum levels of osteoregulatory hormones such as insulin and osteocalcin were monitored. To assess oxidative stress, Malondialdehyde (MDA) serum levels were also determined by ELISA. Once diabetes was successfully induced, rats were grouped according to strain and age at termination. Termination age was at 20 weeks and 28 weeks . The Sprague Dawley (SD) rats were the controls, while the Zucker Diabetic Sprague Dawley rats (ZDSD) were the experimental groups. These were designated as SD20WK (n=8) and ZDSD20WK (n=7) respectively. Another batch was designated as SD28WK (n=8), and ZDSD (n=15) that were terminated at 28 weeks of age. The latter were further divided into moderate diabetes (ZDSD28WK-MOD) (n=9) and severe diabetes (ZDSD28WK-SVD) groups (n=6). Bilateral humeri and femora were harvested then fixed in 10% buffered formalin. Right proximal femora and humeri were scanned using a 3D-μCT scanner (Nikon XTH 225L) to analyse trabecular morphometric parameters, cortical bone area and medullary canal area. Biomechanical strength was analyzed by three point bending tests using a universal tensile tester. Left proximal femora and humeri were processed for histology. Some sections were stained with Haematoxylin and Eosin (H&E) to assess normal histologic morphology and adipocyte quantification. Remnant sections were immunolabelled using the anti-TRAP and anti-ALP antibodies for osteocyte and osteoblast quantification respectively, to assess osteolysis and osteogenesis. Immunolocalization of AGEs, TGF-β1 and BMP3 was also conducted to investigate their role in diabetic skeletopathy. We found that diabetes affected osteoblastogenesis as measured by ALP positive cells and bone marrow adipocytes. TRAP positive osteocytes numbers were increased in the presence of T2D, suggesting an increased osteolysis. There was reduced TGFB1 expression with increased BMP3 expression. The number of AGEs immuno-positive cells as well as its extracellular expression was increased. Our finding suggest that osteoblast and osteocyte numbers are regulated by TGFβ1 and BMP3 in both bones, under the influence of AGEs. Our findings from osteometry, 3-point bending tests and Micro CT support that diabetes weakens bone. The diabetic effect results in lighter, shorter hollow bones that perform poorly under loading, as well as exhibit unfavourable trabeculae microarchitecture. Our findings confirm that T2D causes increased fragility in the proximal femur and humerus as well the mid-diaphysis. These perturbations occur early and late in the disease, and they are also exacerbated by the presence of hyperglycemia. We conclude that the ZDSD rat can be used as a translational model for diabetic skeletopathy at cellular and molecular level, and it can be extrapolated to humans after consideration of other factors like, basal metabolism, age, sex and skeletal loading patterns. We recommend optimal control of blood glucose levels at all stages of the disease to reduce the incidence of fractures in diabetic patients.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Health Sciences, School of Anatomical Sciences, University of the Witwatersrand, Johannesburg, 2022.
Keywords: Type 2 diabetes; ZDSDRAT; Femul proximal; Humerus proximal; Osteogenetic cytokine; Anti-osteogenetic cytokine; Bone marrow adiposity; Micro-CT; 3 point bend; Osteoclastogenesis; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education